Adapting to climate change through crop choice by small and medium farmers in Southern zone of Tamil Nadu, India (SAARC Journal of Agriculture, 2014)
Unpredictable changes in the climate can have a significant impact on crop yield in India in general and in particular in the climate vulnerable state of Tamil Nadu.  This study evaluates how farmers in the Sothern Zone of Tamil Nadu adapt crop change as a technique to cope with uncertainty in crop yield. Three districts in the Sothern Zone, viz., Virudhunagar, Thoothukudi and Thriunelveli districts were adopted for this study. The sample size was equally distributed with 60 households randomly selected and who actively engage in agriculture. The results derived from the Multinomial Logit Model indicate that older farmers were more likely to choose sorghum, groundnut and less likely to choose maize, fruits and vegetables. Education had positive and significant influence on growing sorghum groundnut and chillies. Fruits and vegetables are more likely to chosen if farmer has large acreage. The climate variables seem to have neutral effect for sorghum and groundnut, hence farmers lend to choose theses crops for price stability.  Farmers are most likely to prefer sorghum, cotton, maize and groundnut when income increases from other non-farm sources. When temperature increases by 1oC, farmers more often tend to choose pulses, sorghum, chilli and groundnut. If precipitation increases by 1 cm, farmers choose to cultivate pulses, maize, cotton, fruits and vegetable. Farmers adaptations may vary across agro climatic zones of Tamil Nadu. Hence local government policies and programs in agriculture should have a built in component to address the climate change issues. DOI: http://dx.doi.org/10.3329/sja.v12i1.21120 SAARC J. Agri., 12(1): 139-149 (2014)